LONELINESS AND RELATIONAL MOBILITY WITH PROBLEMATIC INTERNET USE IN COLLEGE STUDENTS - Pratiwi, Ananda; Noviekayati, I. G. A. A.; Pratitis, Niken Titi (Ridwan Institute, 2024)
The rapid development of information and communication technology in addition to having a positive impact such as providing convenience in finding information for students, expanding knowledge, increasing insight, stimulating creativity and learning innovation and allowing wider access to education also has a negative impact such as various misuses of internet technology, such as excessive use to play games, reduced focus while studying which can result in decreased academic performance. One of the negative impacts that quite a lot occurs is Problematic internet use that can occur to anyone when the duration or activity used by individuals in accessing the internet is so high that it makes individuals ignore other aspects of their lives. This study aims to determine the relationship between Loneliness and Relational mobility with Problematic internet use in students. The subjects of this study were 250 college students. The sampling technique used in this study was purposive sampling. Data collection in this study used a Google Form. The measuring instruments in this study are problematic internet use, Loneliness, Relational mobility. The results showed that Loneliness and Relational mobility correlated with problematic internet use. There is a positive relationship between Loneliness and problematic internet use. The higher the Loneliness, the higher the problematic internet use. There is a negative relationship between Relational mobility and problematic internet use. The higher the Relational mobility, the lower the problematic internet use.